The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1177/036354659202000219
|View full text |Cite
|
Sign up to set email alerts
|

Knee ligament injuries in volleyball players

Abstract: The authors report a series of 52 cases of serious knee ligament injuries in volleyball players. The most frequent mechanism of injury was landing from a jump in the attack zone. Women were more affected than men. Injuries were more frequent during games than training. Volleyball must then be considered among high-risk sports according to the frequency and gravity of our surgical findings. Results are similar to those obtained in athletes in other sports who underwent the same surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
125
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(135 citation statements)
references
References 4 publications
6
125
0
4
Order By: Relevance
“…38 For the DVJ, the participant was positioned on top of a 31-cm box and instructed to drop off the box, with both feet leaving the box simultaneously and each foot landing on a separate force platform (AMTI, Watertown, MA), then to immediately execute a maximal effort vertical jump towards an overhead target (FIGURE 1). Athletes frequently injure their ACL while landing from a jump 5,15 ; therefore, the landing phase of the DVJ was used for analysis. In addition, the DVJ task was examined extensively in a population of healthy athletes to determine predictors of initial ACL injury in these populations.…”
Section: Testing Protocolmentioning
confidence: 99%
“…38 For the DVJ, the participant was positioned on top of a 31-cm box and instructed to drop off the box, with both feet leaving the box simultaneously and each foot landing on a separate force platform (AMTI, Watertown, MA), then to immediately execute a maximal effort vertical jump towards an overhead target (FIGURE 1). Athletes frequently injure their ACL while landing from a jump 5,15 ; therefore, the landing phase of the DVJ was used for analysis. In addition, the DVJ task was examined extensively in a population of healthy athletes to determine predictors of initial ACL injury in these populations.…”
Section: Testing Protocolmentioning
confidence: 99%
“…Not surprisingly, the incidence of ACL injury is relatively high in sports involving a high frequency of landing, decelerating and rapid changes of direction such as basketball, netball, handball and volleyball (Arendt and Dick, 1995;Griffin, Angel, Albohm, et al 2000). The incidence of non-contact ACL injury has been reported to be 6 to 8 times greater in females than in males competing in the same sports (Arendt and Dick 1995;Chandy and Grana 1985;Ferretti, Papandrea, Conteduca, et al 1992;Gray, Taunton, McEnzie, et al 1985;Gwinn, Wilkens, McDevitt, et al 2000;Lindenfeld, Schmitt, Hendy, et al 1994;Malone, Hardaker, Garrett, et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, injury of the ACL has been reported to be two to eight times higher in women than in men participating in the same sports. Previous studies have indicated noncontact mechanisms as the reason for ACL tears in women, which make these injuries even more perplexing [1,2,4,7,8,12,20].…”
Section: Introductionmentioning
confidence: 99%